MILLENNIAL GENERATION UTILIZING SOCIAL MEDIA INSTAGRAM @LAMBE_TURAH IN REPORTING VIOLENCE AGAINST WOMEN (Karya Ilmiah Mahasiswa (KIMA), 2024)
The purpose of this study is to determine the millennial generation's choice of news on Instagram @Lambe_Turah on news of violence against women and the millennial generation's response to the news of violence against women on the @Lambe_Turah Instagram account. This research uses qualitative research methods with new media theory and uses and gratifications theory. The research was conducted by collecting data through interviews. The research was located at Indonesian Muslim University. The results showed that the millennial generation made a choice of news about violence against women on the @Lambe_Turah Instagram account because it is one of the popular platforms with various types of content, including news about violence against women and the @Lambe_Turah Instagram account is also one of the Instagram accounts that is widely followed by the millennial generation because of its ability to reveal and discuss gossip and other facts about the lives of artists, figures, public figures and information that is going viral, including information about violence against women. The millennial generation's response to the news of violence against women on the @Lambe_Turah Instagram account shows a sense of empathy, concern and a desire to broaden their understanding of the issue,